Analysing Parallel Interaction in Supply Chains: A Supply Chain Network Perspective - Simangunsong, Elliot (International Research Journal of Business Studies, 2013)
Supply chain management refers to managing a serial chain of businesses which typically consists of retailer, distributor, manufacturer and supplier. However, the businesses in each tier also interact with other channels in the supply chain. These interactions are called parallel interactions and they can directly affect the traditional, serial interactions of a single supply chain. Serial and parallel interactions in a supply chain increase levels of complexity and uncertainty. As a result, it is important to move analysis from dyadic to supply chain network perspective to understand the issues better. The main objective of this study is to investigate parallel interaction issues and how it affects supply chain performance. An empirical study has been conducted in the food industry in Indonesia with inter-related companies. A two stages semi-structured interviews, with top executives from sampled companies have been conducted. The result of analysis helps to clarify previous studies and provide a better understanding of parallel interaction as a genuine source of uncertainty at supply chain level. Three strategies were also identified to effectively manage the issues caused by parallel interaction